B‐cell‐intrinsic function of TAPP adaptors in controlling germinal center responses and autoantibody production in mice. Issue 2 (21st December 2016) - Jayachandran, Nipun; Landego, Ivan; Hou, Sen; Alessi, Dario R.; Marshall, Aaron J.
Abstract : Uncoupling of the tandem PH domain containing proteins (TAPPs) from their ligand PI(3, 4)P2 in B cells results in chronic B‐cell activation and dysregulated germinal centers (GC). This uncoupling leads to autoantibody production that is dependent on GCs. This study reveals a novel PI(3, 4)P2–TAPP dependent regulatory feedback controlling GC responses and restraining autoimmunity. Abstract : Control of B‐cell signal transduction is critical to prevent production of pathological autoantibodies. Tandem PH domain containing proteins (TAPPs) specifically bind PI(3, 4)P2, a phosphoinositide product generated by PI 3‐kinases and the phosphatase SHIP. TAPP KI mice bearing PH domain‐inactivating mutations in both TAPP1 and TAPP2 genes, uncoupling them from PI(3, 4)P2, exhibit increased BCR‐induced activation of the kinase Akt and develop lupus‐like characteristics including anti‐DNA antibodies and deposition of immune complexes in kidneys. Here, we find that TAPP KI mice develop chronic germinal centers (GCs) with age and show abnormal expression of B‐cell activation and memory markers. Upon immunization with T‐dependent Ag, TAPP KI mice develop functional but abnormally large GCs, associated with increased GC B‐cell survival. Disruption of chronic GCs in TAPP KI mice by deletion of the costimulatory molecule ICOS abrogate anti‐DNA and anti‐nuclear antibody production in TAPP KI mice, indicating an essential role for GCs. Moreover, TAPP KI B cells are sufficient to drive chronic GC responses and recapitulate the autoimmune phenotype in BM chimeric mice. Our findings demonstrate a B‐cell‐intrinsic role of TAPP–PI(3, 4)P2 interaction in regulating GC responses and autoantibody production and suggest that uncontrolled Akt activity in B cells can drive autoimmunity.